A cyclical period variation detected in the updated orbital period analysis of TV Columbae - Dai, Zhibin (2010)
Two CCD photometries of the intermediate polar TV Columbae are made for obtaining two updated eclipse timings with high precision. There is an interval time ~17 yr since the last mid-eclipse time observed in 1991. Thus, the new mid-eclipse times might offer an opportunity to check the previous orbital ephemerides. A calculation indicates that the orbital ephemeris derived by Augusteijn et al. (Astron. Astrophys. Suppl. Ser. 107:219, 1994) should be corrected. Based on the proper linear ephemeris (Hellier in Mon. Not. R. Astron. Soc. 264:132, 1993), the new orbital period analysis suggests a cyclical period variation in the O-C diagram of TV Columbae. Using Applegate's mechanism to explain the periodic oscillation in the O-C diagram, the required energy is larger than the energy that a M0-type star can afford over a complete variation period of ~31.0(±3.0) yr. Thus, the light travel-time effect indicates that the tertiary component in TV Columbae may be a dwarf with a low mass, which is near the lower mass limit of ~0.08M⊙ as long as the inclination of the third body is high enough. © Springer Science+Business Media B.V. 2010.